2020
DOI: 10.1155/2020/8844031
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and Renal Protective Effects of Oryeongsan in Spontaneously Hypertensive Rats

Abstract: Oryeongsan (ORS), a traditional medicine used to regulate body fluids, has a long history of use as a diuretic in Korea, China, and Japan. ORS is commonly thought to lower blood pressure, but high-quality data on its effects are sparse. The purpose of this study was to determine the antihypertensive and renal protective effects of ORS in rats with hypertension. Spontaneously hypertensive rats (SHR) were divided into two groups with similar mean baseline systolic blood pressure (SBP) and diastolic blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It was also shown that chronic treatment with ORS decreased high blood pressure in renovascular (two-kidney, one-clip (2K1C)) hypertensive and spontaneously hypertensive rats (SHR) [ 8 , 9 ] with a decrease in plasma levels of renin and aldosterone, suppression of the angiotensin II subtype 1 (AT 1 ) receptor mRNA expression, and accentuation of the ACE2 mRNA expression in the ventricular myocardium from SHR [ 9 ]. These reports suggest that ORS improves the function of the cardiorenal system.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that chronic treatment with ORS decreased high blood pressure in renovascular (two-kidney, one-clip (2K1C)) hypertensive and spontaneously hypertensive rats (SHR) [ 8 , 9 ] with a decrease in plasma levels of renin and aldosterone, suppression of the angiotensin II subtype 1 (AT 1 ) receptor mRNA expression, and accentuation of the ACE2 mRNA expression in the ventricular myocardium from SHR [ 9 ]. These reports suggest that ORS improves the function of the cardiorenal system.…”
Section: Introductionmentioning
confidence: 99%
“…Goreisan (GRS), traditionally known as a diuretic, is an approved Kampo medicine in Japan with indications for headache, oedema, and diarrhoea [21]. It is clinically effective in treating headaches and chronic subdural haematoma [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cerebral oedema formation in AQP4 knockout mice is mild [20]. Hence, suppressing AQP4 function could inhibit cerebral oedema formation.Goreisan (GRS), traditionally known as a diuretic, is an approved Kampo medicine in Japan with indications for headache, oedema, and diarrhoea [21]. It is clinically effective in treating headaches and chronic subdural haematoma [22][23][24][25].…”
mentioning
confidence: 99%
“…Hence, suppressing AQP4 function could inhibit cerebral oedema formation. Goreisan (GRS), traditionally known as a diuretic, is an approved Kampo medicine in Japan with indications for headache, oedema, and diarrhoea [21]. It is clinically effective in treating headaches and chronic subdural haematoma [22][23][24][25].…”
mentioning
confidence: 99%